EPIDEMIOLOGY AND MORPHOLOGICAL ANALYSIS OF SKIN TUMORS AND NON-NEOPLASTIC LESIONS IN A TERTIARY CARE SETTING. - Dr. A.N Bagate; Dr. Shivkanya Kale (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Skin and adnexal lesions encompass a wide spectrum of neoplastic and non-neoplastic conditions that often present diagnostic challenges due to their overlapping clinical and histological features. Accurate histopathological evaluation is essential for proper diagnosis, particularly in distinguishing between benign, malignant, and inflammatory lesions. This study aims to analyze the epidemiological trends and morphological patterns of skin and adnexal lesions in a tertiary care setting over a two-year period. Methods: A retrospective analysis of biopsy specimens diagnosed as skin and adnexal lesions was conducted in the Department of Pathology from November 2016 to October 2018. A total of 149 cases were analyzed for histopathological patterns, age and sex distribution, and relative proportions of neoplastic and non-neoplastic lesions. Specimens were processed using hematoxylin and eosin (H&E) staining, and additional stains were used when required. The lesions were categorized into neoplastic (benign and malignant) and non-neoplastic groups. Results: Among 9,860 biopsy specimens, 149 (1.51%) were diagnosed as skin and adnexal lesions. Neoplastic lesions accounted for 133 cases (89.26%), of which 93 (69.92%) were benign and 40 (30.08%) were malignant. Benign lesions predominantly included soft tissue tumors (30.1%) and adnexal tumors (25.8%). Malignant lesions were mainly epidermal tumors (60%), with squamous cell carcinoma being the most frequent (42.5%). Non-neoplastic lesions constituted 16 cases (10.74%), with granulomatous inflammation being the most common subtype (18.75%). Age-wise, benign lesions were most prevalent in the 41–60 years group (40.9%), malignant lesions in 61–80 years (22.1%), and non-neoplastic lesions in 21–40 years (26.8%). Conclusion: This study highlights the diverse spectrum of skin and adnexal lesions in a tertiary care setting, emphasizing the critical role of histopathology in their accurate diagnosis. The findings underscore the predominance of benign neoplastic lesions and the importance of early detection and differentiation of malignant and non-neoplastic conditions for effective clinical management.